2015
DOI: 10.1530/eje-15-0155
|View full text |Cite
|
Sign up to set email alerts
|

MANAGEMENT OF ENDOCRINE DISEASE: Diabetes and osteoporosis: cause for concern?

Abstract: Diabetes and osteoporosis are both frequent conditions, and they may thus occur simultaneously by chance. However, a growing body of evidence suggests that hyperglycemia may impair bone matrix formation and biochemical competence. Decreased biomechanical competence may be present even in a setting of increased bone mineral density, as assessed by traditional dual energy X-ray absorptiometry or normal structural parameters by quantitative computed tomography. Also, the absence of endogenous insulin secretion in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 64 publications
(71 reference statements)
4
43
0
Order By: Relevance
“…One reason for this was the deposition of bone collagen induced by AGEs. Then, osteoblasts can't adhere to collagen and the activities and maturation of osteoclast increased, which resulted in the decrease of BMD and maximum cross-sectional area of callus and may finally become osteoporosis [26,27]. Our study further confirmed that the bone remodeling was affected by the diabetes mellitus, contributing to the delayed fracture healing.…”
Section: Discussionsupporting
confidence: 69%
“…One reason for this was the deposition of bone collagen induced by AGEs. Then, osteoblasts can't adhere to collagen and the activities and maturation of osteoclast increased, which resulted in the decrease of BMD and maximum cross-sectional area of callus and may finally become osteoporosis [26,27]. Our study further confirmed that the bone remodeling was affected by the diabetes mellitus, contributing to the delayed fracture healing.…”
Section: Discussionsupporting
confidence: 69%
“…11 In the absence of insulin, there are increased levels of OPG and decreased RANKL. 32ā€“35 Underlying microvasculopathy, decreased vitamin D levels, inflammation, and increased levels of advanced glycation end products further contribute to impaired bone health. 28,32 …”
Section: Pediatric Bone Health: Type 1 Diabetes Mellitusmentioning
confidence: 99%
“…This finding is explained with lack of insulin in T1DM patients and could account for higher risk of osteopenia and osteoporosis in young age T1DMs [24]. Nevertheless higher BMD levels which have been reported in patients with T2DM in comparison with patients with T1DM could be explained by higher body weight levels and BMD in the T2DM patients [25]. …”
Section: Main Textmentioning
confidence: 99%